Adolescent Marriage in Nepal: A Subregional Level Analysis. Issue 4 (19th May 2017) - Guragain, Arjun Mani; Paudel, Binita Kumari; Lim, Apiradee; Choonpradub, Chamnein
ABSTRACT: This study aims to identify the distribution of marriages among adolescents, aged 10 to 19 years, throughout Nepal. Data were obtained from the 2011 Nepal Demographic and Health Survey. Chi-square tests and logistic regression analyses were used to identify the main determinants of adolescent marriages (AMs). Of a total 11, 967 weighted samples, 9.3% of adolescents (95% CI, 8–10%) were found to have been married; a significantly higher percentage of these were female. The variability of AMs varied among the regions of Nepal, with a higher percentage occurring in the Western Mountain, Mid-Western Hill, and Central Terai areas. AMs were also more likely to have occurred among poorer households. The findings show a substantial differences of AMs in different geographic areas and demographic levels in Nepal.